Pembuatan Aplikasi Sistem Electronic Contractor Safety Management System (E-CSMS) Berdasarkan Pedoman CSMS PT. XYZ - Maulana Harry Wiryanta; Wiryanta Wiryanta (JURAL RISET RUMPUN ILMU TEKNIK, 2026)
PT. XYZ faces administrative challenges in implementing the Contractor Safety Management System (CSMS), which has been managed manually from risk assessment and pre-qualification to contractor selection resulting in validation delays, document duplication, and limited monitoring. This study aims to: (1) identify the constraints of the manual CSMS at PT. XYZ; (2) design an electronic-CSMS (e-CSMS) application tailored to internal user needs; (3) analyze the contribution of e-CSMS to document management effectiveness; and (4) evaluate the design's alignment with the Occupational Health and Safety Management System (SMK3) principles as per Government Regulation No. 50 of 2012. The method employed is Research and Development (preliminary stage) using a descriptive qualitative approach through interviews, observations, and document studies. The design results include: (i) a unified digital form integrating procurement data input, risk assessment entries (severity and probability), and document upload and assessment for pre-qualification/selection in a single workflow; (ii) a monitoring dashboard with filtering and export functions; and (iii) internal access settings within PT. XYZ's HSSE portal. Functionally, this design addresses the main bottlenecks of the manual process by creating a more concise, structured, and documented verification workflow, thereby making document management more efficient and traceable. In terms of compliance, e-CSMS supports the implementation of SMK3 elements in the administrative domain of policy establishment, planning, and execution of OHS plans through consistent recording and verification mechanisms. Development recommendations include expansion to field implementation phases, automation of risk-level calculations, and an option for preliminary data entry by contractors with final verification remaining with the internal team.